UJI TOKSISITAS EKSTRAK ETANOL UMBI TALAS (Colocasia esculenta L. Schoot ) DENGAN METODE BRINE SHRIMP LETHALITY TEST TERHADAP Artemia Salina Leach - Bayu Putra; Said Asrul Adjmi Assagaf (Fakultas Farmasi UMI, 2015)
The research of toxicity assay of Ethanol Extracts of Taro tubers (Colocasia esculenta L. Schott) have been conducted with the aim of determining the effects of toxicity and anticancer potential of ethanol extract of tubers of taro (Colocasia esculenta L. Schott) by Brine Shrimp Lethality Test method against Artemia salina Leach. Ethanol extract, made with concentrations of 0.1, 1, 10, 100, 1000, and 10000 µg/ml and for comparison with the drugs vincristine concentrations of 0.01, 0.1, 1, and 10 µg/ml. Negative control using sea water made with the same concentrations. Furthermore, each concentration 10 ml of sea water and then put 10 shrimp larvae. The treatment is done by 10 replication at each concentration. Observations were made after 24 hours of treatment by counting the number of dead larva. The observations calculated using probit analysis program, showed LC50 values with 95% confidence level is 33,997 µg/ml (7,970 µg/ml-151,231 µg/ml). And the results of a comparison of data from drug vincristine showed LC50 value is 0,398 µg/ml (0,259 µg/ml-0,624 µg/ml).